Kajian Narrative terhadap Profil Farmakokinetik Antibiotik pada Pasien Kritis: Implikasi terhadap Ketercapaian Target Farmakokinetik-Farmakodinamik - Setiawan, Eko; Widyati,; Marpaung, Ferdy Royland; Sukandar, Edy; Susaniwati,; Lukas, Dwi Lily; Wijono, Heru; Warindra, Taufin; Kurniawan, Roni; Wibowo, Tjipto; Hendradi, Wahyu; Costa, Menino Osbert; Aziz, Mohd-Hafiz Abdu; Roberts, Jason (Pharmaceutical Sciences and Research, 2019)
The severity of diseases, the complexity of treatment, and the use of medical devices in the intensive care unit (ICU) may change the pharmacokinetics (PK) profile of antibiotics among critically ill patients.This narrative review aims to explain the PK profile of critically ill patients compared to other group of patients and to describe the pharmacokinetic-pharmacidynamic (PK-PD) target attainment among this group of patients. Only articles published less than 10 years ago were included in this narrative review. Evidences have indicated that critically ill patients have relatively larger volume distribution (Vd) of hydrophilic antibiotics compared to patients with stable conditions. The fluid shifting to interstitial space, hypoalbuminemia, and aggressive fluid treatment may contribute to the increase value of Vd in critically ill patients. The clearance (CL) of hydrophilic antibiotics in critically ill patients is highly determined by dynamic changing of renal function compared to patients in other wards. The phenomenon of augmented renal clearance and the use of high intensity of renal replacement therapy can increase the CL of hydrophilic antibiotics. The different PK profile of antibiotics may lead to the failure of attaining the PK-PD target if the dose of antibiotics is not adjusted according to such differences